Volatile Sedation in Reversible Cerebral Vasoconstriction Syndrome: A Case Report. Issue 2 (15th July 2017) - Ramming, Michael; Bansbach, Joachim; Beck, Christopher; Kalbhenn, Johannes
Abstract : Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by reversible multifocal narrowing of cerebral arteries heralded by sudden (thunderclap) headaches with or without neurological deficits, resolving within 3 months. It often occurs in the peripartum period. To date, the ideal treatment remains unclear. Here, we report the case of a 31-year-old primigravida who presented with intracranial hemorrhage and went on to develop RCVS and acute respiratory distress syndrome over the course of her illness. Her condition was further complicated by uterine atony and septic shock. We describe for the first time the use of short-acting volatile sedation for prone positioning in acute respiratory distress syndrome during RCVS.